Pauvreté des liens d’attachement et déficiences dans les rapports intimes chez les agresseurs sexuels - Marshall, W. (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1994)
The nature of parent/child attachments is described and their effects on adolescent and adult intimacy and loneliness are outlined. Poor quality attachments are said to result in loneliness and deficits in intimacy, and these, in turn, make the individual vulnerable to those influences and circumstances that lead to sexual offending. These processes are one of the most important sets of factors in our more general theory of the etiology and maintenance of sexually offensive behavior. Implications for the assessment and treatment of sex offenders are derived.